2020
DOI: 10.3390/microorganisms8020170
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Variation and Stability of Bacterial Communities in Tomato Rhizosphere Microbiota

Abstract: Microorganisms that colonize the plant rhizosphere can contribute to plant health, growth and productivity. Although the importance of the rhizosphere microbiome is known, we know little about the underlying mechanisms that drive microbiome assembly and composition. In this study, the variation, assembly and composition of rhizobacterial communities in 11 tomato cultivars, combined with one cultivar in seven different sources of soil and growing substrate, were systematically investigated. The tomato rhizosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 53 publications
7
29
2
Order By: Relevance
“…Complete information on unique and shared OTUs is available ( Supplementary Table S3 ). In comparison to our result, another study identified a bacterial tomato rhizosphere core microbiome composed of 68 orders using different tomato cultivars in a single soil, and 27 orders using a single tomato genotype in five soils ( Cheng et al, 2020 ).…”
Section: Resultscontrasting
confidence: 56%
“…Complete information on unique and shared OTUs is available ( Supplementary Table S3 ). In comparison to our result, another study identified a bacterial tomato rhizosphere core microbiome composed of 68 orders using different tomato cultivars in a single soil, and 27 orders using a single tomato genotype in five soils ( Cheng et al, 2020 ).…”
Section: Resultscontrasting
confidence: 56%
“…The communities sequenced in this study were dominated by bacteria of the phyla Bacteroidetes and Proteobacteria. Other studies conducted on tomato plants report a community dominated by Proteobacteria [ 50 , 51 , 52 , 53 , 54 ] and Ascomycota, the dominant fungal phylum in this study [ 53 ]. In addition, Bacteroidetes have been observed previously in similar abundance in the tomato rhizosphere [ 51 , 54 ].…”
Section: Discussionsupporting
confidence: 56%
“…Rhizosphere microorganisms could contribute to plant health, growth and productivity (Cheng et al 2020; 6 Gene profiles of the bacterial community in P. ludlowii tissues and rhizosphere soil predicted using PICRUSt Mendes et al 2013). However, some important microbial groups, such as Pseudomonas and Bacillus, decreased with soil depth.…”
Section: Discussionmentioning
confidence: 99%